Productivity and Remuneration of Labour: Disparities Across Sectors And Countries - Hamulczuk, Mariusz; Rembisz, Włodzimierz (Olsztyn Economic Journal, 2017)
The aim of this paper is to investigate the relationship between labour productivity and labour remuneration among agricultural and non-agricultural sectors in selected EU countries. The issue under investigation pertains to the question of whether remunerations for labour and their rate of growth are attributable to changes in labour productivity. The problem is analyzed via static and dynamic approaches. To carry out the research, the authors’ own analytical approach is used, while appropriate statistical data for 1995–2013 and methods are used to verify the hypothesis. The conclusion of the study is that the relationship between remuneration and productivity substantially differ across sectors and countries. Especially in the agricultural sector, one can observe that the level of remuneration and growth are weakly related to productivity growth.